Penerapan Algoritma A* (Star) pada Lokasi Cafe Instagramable di Kota Binjai Berbasis Android - Pane, Elly Supiah; Samsudin, Samsudin (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The speed of an internet network makes geographic information systems easy to use by all groups, including the process of Instagrammable cafe mapping. With this system, it will help to make it easier for consumers to find cafe locations, help convey detailed cafe information and also become an Instagrammable promotional media for cafes in Binjai City. In the system design process, the method chosen as the development method is waterfall, and uses object-oriented modeling, namely UML and uses the A Star Algorithm to determine the closest distance from the user to the cafe they are going to. With this geographic information system, it will make it easier for consumers to get locations and information about Instagrammable cafes in Binjai City and also save consumers' time and become a promotional medium for the Binjai City Tourism Office and for the cafe owners.